Lendo a bíblia como literatura: análise de Marcos 5. 21-43 - Miranda, Carlos Roberto (2020)
The main goal of this work is to apply the literary methods of narrative analysis of the Gospel of Mark, especially in chapter 5, verses 21 to 43. The narrative of Mark was chosen because it was seen, by many scholars, as being a work without many attractions that respect literary art. In this literary analysis carried out, the usual narrative elements were examined: characters, scenery, time, plot. Based on these elements, the research was developed to analyze the role of the “narrator”, as well as his relationship with the narrative time and with the focalization technique or point of view. Understanding the importance of the “narrator” in the Gospel of Mark is a differential in the sense that a good understanding of the book. A literary analysis of some of the literary resources marked in the narrative revealed a greatness of his style, a sense of his purposes and a cohesion of the work. Finally, when considering an art of the narrative of the text of the Gospel of Mark, not only does the book become much more extraordinary for its readers, but its theological and moral meanings become more available.